Stationary Josephson effect in a weak-link between nonunitary triplet superconductors - Rashedi, G.; Kolesnichenko, Yu.A. (Физика низких температур, 2005)
A stationary Josephson effect in a weak-link between misorientated nonunitary triplet superconductors
is investigated theoretically. The non-self-consistent quasiclassical Eilenberger equation
for this system has been solved analytically. As an application of this analytical calculation,
the current-phase diagrams are plotted for the junction between two nonunitary bipolar f-wave
superconducting banks. A spontaneous current parallel to the interface between superconductors
has been observed. Also, the effect of misorientation between crystals on the Josephson and spontaneous
currents is studied. Such experimental investigations of the current-phase diagrams can be
used to test the pairing symmetry in the above-mentioned superconductors.